2011
DOI: 10.1016/j.jhazmat.2011.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide risk assessment in flower greenhouses in Argentina: The importance of manipulating concentrated products

Abstract: An evaluation of the Potential Dermal Exposure of workers to endosulfan and procymidone at the mix/load and application stages was done in small floricultural production units in Argentina. Seven experiments were performed with different operators under typical greenhouse conditions, based on the whole body dosimetry methodology. These results indicate that the mean Potential Dermal Exposure of the application step was 45.0 ± 55.0 mL h(-1) with the highest proportion on torso, head, arms and hands. When the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…However, our study showed a low level (or absence) of producer protection. The few producers who used masks and gloves wore them during the application of pesticides but not during the preparation of the mixture when the greatest exposure occurs because the product is handled in the concentrated state and the risk of inhalation of concentrated pesticide vapors remains high [ 8 , 40 , 41 ]. 64% of hand contamination occurred during the mixing-loading phases [ 36 ], 20% of producers’ wore short-sleeved clothing and shorts, while several studies have highlighted heavy contamination of legs and forearms during pesticide application [ 36 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our study showed a low level (or absence) of producer protection. The few producers who used masks and gloves wore them during the application of pesticides but not during the preparation of the mixture when the greatest exposure occurs because the product is handled in the concentrated state and the risk of inhalation of concentrated pesticide vapors remains high [ 8 , 40 , 41 ]. 64% of hand contamination occurred during the mixing-loading phases [ 36 ], 20% of producers’ wore short-sleeved clothing and shorts, while several studies have highlighted heavy contamination of legs and forearms during pesticide application [ 36 , 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of pesticide solutions for droplet drift assessment is the most reliable method. However, the organic solvent is usually chosen to extract pesticide active ingredients from the samples in the laboratory, such as hexane [30][31][32] and acetone [33]. The extensive use of organic solvent, their waste disposal, and a high-frequency repetitions at the experimental site not only harms the environment but also has a health hazard for laboratory personnel.…”
Section: Spray Liquidmentioning
confidence: 99%
“…Endosulfan, chlorpyrifos, procymidone, trifluralin and deltamethrin were chosen for this study due to their extensive use in horticultural and floricultural production units in Argentina (Berenstetin et al, 2014;Flores et al, 2011;Hughes et al, 2008;Querejeta et al, 2012;Querejeta et al, 2014;Ramos et al, 2010). Additionally, endosulfan was selected for swabbing and immersion experiments due to its high stability.…”
Section: Pesticidesmentioning
confidence: 99%